Agripreneurship through Krishi Vigyan Kendras: A Meta-analysis of Qualitative Case Studies - Shreekant Sharma , K. Suryaprakash Goud; Ram Datt (Indian Journal of Extension Education, 2017)
India is an agricultural based economy and about 50 per cent of population is engaged in agriculture. The role of agricultural extension in the sustainable development of rural areas has not been fully utilized. New initiatives in the form of decentralization and Convergence; participatory approaches to extension, and the use of ICT tools have been taken to improve the efficiency and effectiveness of the service. Entrepreneurship and skill development is seen as a new and effective way for livelihood generation in the country. It is supposed to solve many problems of migration, low value addition in agri-products, unemployment and many more. Krishi Vigyan Kendras (KVKs) are important agri extension functionaries within the district and has multifaceted roles. They have created many success stories in agripreneurship. This paper recommends replication of success methods practiced by KVKs actively promoting agripreneurship by other KVKs. In addition, Agri Business Development Cell in the KVK could have a multidimensional approach for liasioning with Business Planning and Development (BPD) units of SAUs and business development service providers for promotion and development of innovation based enterprises.